The Influence of Gadget Usage on the Lack of Face-to-Face Communication among 11th Grade Students at SMAN 1 Badegan, Ponorogo - Nurul Syafikah*; Akhmad Rifa’i (Universitas Syiah Kuala, 2023)
In this era of globalization, all circles, especially students, are familiar with super-sophisticated technology commonly referred to as gadgets. This rapid development will certainly change the pattern of communication, which previously communicated directly to communication using gadgets. One of the negative impacts in this case is that students then become indifferent to the surrounding environment and are more concerned with playing gadgets. The purpose of this paper is to examine the effect of gadget use on the lack of face-to-face communication among students in class XI at SMAN 1 Badegan Ponorogo. The approach in this study is a quantitative approach. The data collection technique used was a questionnaire. The data analysis used was simple linear regression test. The population in this study were grade XI students totaling 349 students and the sample used was purposive sampling with a total of 80 respondents. The results of this study found that there was a significant influence of gadget use on the lack of face-to-face communication in class XI students at SMAN 1 Badegan Ponorogo with a result of 37.4%. This study was only conducted at SMAN 1 Badegan Ponorogo, it would be better if more samples were used to deepen the information to find out other impacts caused by the use of gadgets.